2006
DOI: 10.3386/w11948
|View full text |Cite
|
Sign up to set email alerts
|

Intangible Capital and Economic Growth

Abstract: Published macroeconomic data traditionally exclude most intangible investment from measured GDP. This situation is beginning to change, but our estimates suggest that as much as $800 billion is still excluded from U.S. published data (as of 2003), and that this leads to the exclusion of more than $3 trillion of business intangible capital stock. To assess the importance of this omission, we add capital to the standard sources-of-growth framework used by the BLS, and find that the inclusion of our list of intan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
257
0
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(273 citation statements)
references
References 47 publications
(11 reference statements)
4
257
0
11
Order By: Relevance
“…Such applications the transition to a market economy, the introduction of ICT capital in the production process, and the increasing employment of weightless assets such as advertising goodwill and research and development knowledge. (Corrado, Hulten, and Sichel (2006)) Both proposed alternatives to the Solow-Thörnqvist meaures can be thought of as a "marginalization" of the error carried forward by the capital stock across time. Most recent investment is most likely to be properly valued at acquisition cost and to be fully utilized.…”
Section: Resultsmentioning
confidence: 99%
“…Such applications the transition to a market economy, the introduction of ICT capital in the production process, and the increasing employment of weightless assets such as advertising goodwill and research and development knowledge. (Corrado, Hulten, and Sichel (2006)) Both proposed alternatives to the Solow-Thörnqvist meaures can be thought of as a "marginalization" of the error carried forward by the capital stock across time. Most recent investment is most likely to be properly valued at acquisition cost and to be fully utilized.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, they have long-term relationships with the firm -a convenient way to develop firm-specific expertise -while their interests remain a priori distinct from those of the executive managerial team. On the other hand, workforce training in firm-specific capabilities and labor organization are two of the main components of intangible performance drivers: Corrado et al (2006) estimate in the US case for the period 1995-2003 that investments aimed at enhancing human resources (training, labor organization including strategic planning) accounted for one third of total investment in intangible assets. Furthermore, while they observe that, for the same period, investments in intangibles accounted for 27% of the annual growth, they note that the contribution of training and organizational innovation amounts to one third of this 27%.…”
Section: Board Independence and Firm-specific Expertise: The Tradmentioning
confidence: 99%
“…For example, Gourio and Rudanko (2014b) proxy selling, general and administrative expenses (S&GA) for investment in customer capital, while Tronconi and Marzetti (2011) and Eisfeldt and Papanikolaou (2014) proxy S&GA for investment in organisational capital. Although this assumption is often found to be invalid, it is the best this study could adopt based on the available data; and, if this assumption is true, the study will avoid the inaccurate measurement problems found in Corrado et al (2009) and Fukao et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike Corrado et al (2009), Fukao et al (2009 and Hulten and Hao (2012), however, this study uses a proxy approach-that is, we use the entries relevant to intangible investment as proxies and make the assumption that the ratios of intangible investments to the proxies remain constant over time. Using the proxy approach and assuming the ratio of true value to proxies is constant over time are also common in the literature on intangible capital.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation